The Thing Between : Internationales Kunstprojekt - Techischen Sammlungen, Dresden; Boden, Roland; Cremers, Ehrhardt; Daniels, Dieter; Flusser, Vilém; Janecke, Christian; Lindner, H.; Ströhl, Andreas (Dresden : Kulturamt Dresden, 1996)
Allamoda, Bettina ; Boden, Roland ; Cerny, David ; Deutschbauer, Julius ; Gärtner, Ulrike ; Gustar, Milan ; Hasucha, Christian ; Janke, Karl ; Lanz, Eric ; Libera, Zbigniew ; Atelier van Lieshout ; Rádová, Ellen ; Starke, Ipke ; Van Der Straeten, Andrea
biografie
The Thing Between : Internationales Kunstprojekt, Technischen Sammlungen, Dresden, 20.09 - 30.09.1996
Duits
boek